Design and manufacturing of an isogrid structure in composite material: Numerical and experimental results. (20th May 2016) - Sorrentino, L.; Marchetti, M.; Bellini, C.; Delfini, A.; Albano, M.
Abstract: Isogrid structures are constituted by a thin skin reinforced with a lattice structure. Such structures are adopted in aeronautical industry since they present both structural resistance and lightness. These structures were initially made of aluminium and were obtained by milling process. Nowadays, composite materials are used in order to improve the lightness peculiarities of such structures. The aim of this research work was to design an isogrid cylinder, made of composite material, fit to withstand a defined axial load. The design was carried out in two step: in the former, the Vasiliev theory was used to define the rib dimension of the lattice structure, while in the latter both material and thickness of the skin were determined by FEM. Then, the manufacturing process was designed, paying particular attention to the mould design and to the curing process. In fact, the curing tools and the thermal cycle strongly affect the quality of the produced part. Finally, the designed part was produced and tested to assess the quality of the manufacturing process and the correspondence to the design requirements.